'An Entirely Fictitious Importance'? Reconsidering the Significance of the Irish Glove Trade: A Study of Limerick Gloves, 1778–1840. (1st June 2014) - Foley, Liza
Abstract: This essay reconsiders the significance of Ireland's glove trade through a study of the formerly celebrated Limerick gloves. Made from the aborted skins of unborn calves and sold encased in a walnut shell, these gloves are a fascinating example of Irish design. Yet, despite existing in numerous collections across England and Ireland, very little attention has been paid to the study of these artefacts. Tracing their position as a fashionable article of aristocratic dress, this essay demonstrates that Limerick gloves played an important role in both Irish and English dress history. It contends that, not only were the gloves instrumental in demonstrating aristocratic ideals of propriety and decorum, but they also impacted other regional glove manufacturing as a result of their desirability.